A study on factors influencing house purchasing behavior amongst customers in Malacca / Mohd Ammar Aflus and Siti Nurul Hidayah Mohd Aripin - Aflus, Mohd Ammar; Mohd Aripin, Siti Nurul Hidayah (Faculty of Business and Management, 2014)
These researches focus on the relationship between house purchasing with personal factors, location, product design and price. The purpose of the research is to investigate on the factors influencing house purchasing behavior amongst customers in Malacca. In addition, by doing this research the researchers will know whether there are any significant relationships between variables. The questionnaire was developed and distributed to 100 respondents in Malacca. Frequency distribution, reliability test, correlation analysis and regression analysis has been chosen by using SPSS system to find out the result. The findings indicate that a location is the most factors that influence house purchasing behavior amongst customers than personal factors, product design and price.